Scientific Opinion on Pyrrolizidine alkaloids in food and feed - EFSA Panel on Contaminants in the Food Chain (CONTAM) (Wiley, 2011)
Abstract The European Food Safety Authority (EFSA) was asked by the European Commission to deliver a scientific opinion on pyrrolizidine alkaloids (PA) in food and feed. PAs are toxins exclusively biosynthesised by plants. To date, approximately 600 different PAs are known. Results for 13,280 bulk honey and 1324 retail honey samples were provided to EFSA by one Member State and 351 feed samples were provided by a second Member State. The EFSA Panel on Contaminants in the Food Chain (CONTAM Panel) performed estimates of both acute and chronic exposure to PAs through honey for three different age groups. Although there might be other sources of PA exposure, due to lack of data the CONTAM Panel was not able to quantify dietary exposure from food other than honey. A number of PAs were identified as being of particular importance for food and feed. Based on the present knowledge of metabolism, activation, DNA adduct‐formation, genotoxicity and carcinogenicity, the CONTAM Panel concluded that 1,2–unsaturated PAs may act as genotoxic carcinogens in humans. Therefore, the CONTAM Panel decided to apply the Margin of Exposure (MOE) approach. A benchmark dose lower confidence limit for a 10 % excess cancer risk (BMDL10) of 70 µg/kg b.w. per day for induction of liver haemangiosarcomas by lasiocarpine in male rats was calculated as the reference point for comparison with the estimated dietary exposure. The CONTAM Panel concluded that there is a possible health concern for those toddlers and children who are high consumers of honey. There is generally a low risk of PA poisoning in livestock and companion animals in the EU as most PA poisonings reported recently are due to accidental exposure.